2017
DOI: 10.1177/0735633117731382
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Robotics, More Than Just Working in Groups

Abstract: The purpose of this study was to determine what collaborative interventions produce positive effects for students working on collaborative robotics projects for science process skills, collaborative problem solving, and learning motivation. In addition, the study examined the impact students' prior robotics experience had on science process skills, collaborative problem solving, and learning motivation. The results indicated experience level and collaboration interventions can have impacts on students. Assigne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 25 publications
3
12
0
1
Order By: Relevance
“…This study is aligned with the findings from a study conducted by Zhang, Xu, Yang, Lai, and Wong (2018) who show that using robots as a simulation game increases students' interest in Science and Technology. Similar findings were reported by a study conducted by Taylor and Baek (2018). Researchers think that robot games are of interest to students because the shapes of the robots come in a variety of colors and movements.…”
Section: Discussionsupporting
confidence: 86%
“…This study is aligned with the findings from a study conducted by Zhang, Xu, Yang, Lai, and Wong (2018) who show that using robots as a simulation game increases students' interest in Science and Technology. Similar findings were reported by a study conducted by Taylor and Baek (2018). Researchers think that robot games are of interest to students because the shapes of the robots come in a variety of colors and movements.…”
Section: Discussionsupporting
confidence: 86%
“…A strong relationship between motivation and robotics activities has been reported in the literature. The use of robotics improves students' motivation in STEM education (Kim et al, 2015;Taylor & Baek, 2018), programming courses (Çınar, 2019;McGill, 2012), foreign language education (Hong et al, 2016) and science education (Chin et al, 2014;Koç & Böyük, 2013;Sáez-López et al, 2019;Park, 2015). On the contrary, some research results did not demonstrate any motivational effects from using robots in the classroom (McWhorter & O'Connor, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Alemi et al (2017) found that learners' motivations were stimulated with the increase in active interactions with robots. They could gain a positive influence when using robots to collaborate, and robots could also help educators make use of scientific, strategic, and purposeful robot design programs to improve learners' attitudes toward the robot experience (Taylor & Baek, 2018). Educational robots are considered to be an effective medium to improve self-efficacy, cultivate learners' understanding of scientific concepts, and promote the development of CT (Jaipal-Jamani & Angeli, 2017).…”
Section: Educational Robots In Ct and Language Learningmentioning
confidence: 99%